In-silico based vaccine development: targeting nucleocapsid protein of SARS-CoV-2. - Iva, Yesmine Akter (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.